Distributed Power Generation Scheduling, Modelling and Expansion Planning - Contreras, Javier; Muñoz-Delgado, Gregorio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Distributed generation is becoming more important in electrical power systems due to the decentralization of energy production. Within this new paradigm, new approaches for the operation and planning of distributed power generation are yet to be explored. This book deals with distributed energy resources, such as renewable-based distributed generators and energy storage units, among others, considering their operation, scheduling, and planning. Moreover, other interesting aspects such as demand response, electric vehicles, aggregators, and microgrid are also analyzed. All these aspects constitute a new paradigm that is explored in this Special Issue.